Effect of Temperature, Physical and Chemical Treatments on Seed Quality Enhancement in Senna (Senna alexandrina) - PATEL JR; KALYANRAO PATIL; DA PATEL; PRITYKUMARI (Seed Research, 2026)
Senna is an important medicinal plant which belongs to family Fabaceae. Its seeds attribute lower germination, usually due to seed coat-imposed dormancy. A laboratory experiment was conducted at Department of Seed Science and Technology, BACA, Anand Agricultural University, Anand, Gujarat during 2018-19 to study the effect of temperature, physical and chemical treatments on seed quality enhancement. The experiment was carried out in two different parts. First one to standardize optimum temperature requirements for germination of senna seeds, there were four different temperatures are considered viz. 20°C, 25°C, 30°C and 35°C. The results revealed that temperature 25°C shown higher germination per cent (32.33 %). In the second experiment various physical, chemical and hot water treatments like mechanical scarification, H2SO4 (100%) and 100oC water treatments with different duration were given. The result indicated that mechanical scarification for two minutes increased the germination per cent (94.66%) as compared to control (32.33 %) and also improved seedling growth parameters at 25°C.